New tribe-level classification of Hypostominae (Loricariidae) based on optimization of morphological states on DNA-based relationships, with descriptions of three new tribes and two new genera - Jonathan W. Armbruster; Nathan K. Lujan (Neotropical Ichthyology)
Abstract Hypostominae tribe-level taxonomy is revised with new recognition and cladistic diagnoses of previously proposed family-level names for the Acanthicus (Acanthicini), Chaetostoma (Chaetostomatini), and Hemiancistrus (Spectracanthicini) clades. Three new tribes are described for the Peckoltia, Pseudancistrus,and ‘Pseudancistrus’ clades, with a new tribe erected for two new monotypic genera containing the sister species ‘Pseudancistrus’ sidereus and ‘P.’ pectegenitor. This third new tribe is known only from the upper Orinoco and Negro Rivers and is identifiable by having an accentuated keel on the caudal peduncle formed by dorsal laminae of the ventral plate series being strongly concave. The new genera are distinguishable by ‘P.’ pectegenitor having extremely long cheek odontodes reaching to the third plate of midventral plate series (vs. anterior to opercular opening in ‘P.’ sidereus) and 10 (vs. 7) branched dorsal-fin rays. We re-optimized morphological character-state change by mapping states previously used to infer evolutionary history onto a composite phylogenetic tree inferred from DNA-sequence data. This revealed the strong influence on morphology-based phylogenies of a correlated suite of opercular character states related to the mechanism for cheek odontode eversion. These states appear to be plesiomorphic within Hypostominae and to have been independently lost or reduced multiple times.